STUDY OF THE CHEMICAL COMPOSITION AND ANTIFOULING ACTIVITY OF THE MARINE SPONGE Cliona delitrix EXTRACT - CASTELLANOS H., Leonardo; MAYORGA W., Humberto; DUQUE B., Carmenza (Vitae, 2010)
In a field test for antifouling activity the raw extract and the organic fraction obtained from the marine sponge Cliona delitrix, collected at the San Andrés Islas (Colombia, Caribbean Sea), showed activity. The organic fraction was separated by column chromatography to obtain enriched fractions of glycerides, glycolipids, phospholipids, free fatty acids, fatty acids methyl esters (FAMEs) and monohydroxysterols identified by TLC and dereplication techniques (NMR). The glyceride, glycolipid, and phospholipid fractions were hydrolyzed, and the fatty acids methyl esters obtained, together with the initial fatty acids fraction were converted into their methyl esters and analyzed by HRGC-MS. In order to locate unsaturations and alkyl branches in fatty acids, their methyl esters derivates were transformed to the corresponding pyrrolidides and subsequently analyzed by HRGC-MS. The identification of the marifatty acids was carried out using their ECL value as methyl esters, and particularly the study of their pyrrolidide spectra was used to locate unsaturations and alkyl branch positions. The analysis allowed the identification of 89 fatty acids. The main acids include the new 7,10,12,14-icosatetraenoic acid, as well as 5,9-hexacosadienoic acid and hexadecanoic acid. Additionally, 19 monohydroxysterols were identified by HRGC-MS and NMR 1H. Cholestanol and clionasterol were the most abundant compounds and the stanols presence (near to 30%) was not previously reported for this genus.